Attosecond Strobing of Two-Surface Population Dynamics in Dissociating H2+ - Staudte, A.; Pavičić, D.; Chelkowski, S.; Zeidler, D.; Meckel, M.; Niikura, H.; Schöffler, M.; Schössler, S.; Ulrich, B.; Rajeev, P. P.; Weber, Th.; Jahnke, T.; et al. (My University, 2007)
Using H+2 and D+2, we observe two-surface population dynamics by measuring the kinetic energy of the correlated ions that are created when H+2 (D+2) ionize in short (40–140 fs) and intense (1014 W/cm2) infrared laser pulses. Experimentally, we find a modulation of the kinetic energy spectrum of the correlated fragments. The spectral progression arises from a hitherto unexpected spatial modulation on the excited state population, revealed by Coulomb explosion. By solving the two-level time-dependent Schrödinger equation, we show that an interference between the net-two-photon and the one-photon transition creates localized electrons which subsequently ionize.